Improving Veterinary Clinic Efficiency: Web-Based Appointment Scheduling Application for Veterinary Clinics - Farida, Ida; Suprobo, Arya; Abdilah, Faisal Maulana; Wiguna, Abid Pradipta (Journal Collabits, 2025)
This article presents the development of a website-based application aimed at improving appointment scheduling and service efficiency in a veterinary clinic, specifically addressing the challenges posed by a manual scheduling system that results in long wait times and customer dissatisfaction. The increasing demand for veterinary services, coupled with the shortage of veterinarians in Indonesia, requires innovative solutions to improve operational efficiency. To address these issues, the waterfall methodology was applied for application development, which includes five stages: requirements analysis, design, implementation, testing, and maintenance. The application features a user-friendly interface and efficient backend management, utilizing Next.js for frontend development and Firebase for backend data management. Key functionalities include user login and registration, a responsive homepage, a detailed list of services, an appointment booking system, and a contact page with Google Maps integration. The results show that the application successfully modernizes appointment management, improves communication between pet owners and veterinary staff, and increases overall access to clinic information. The conclusion highlights the effectiveness of the platform in streamlining veterinary services while suggesting future enhancements such as online payment integration, an admin dashboard, enhanced data security, and more extensive user testing to further optimize user experience and operational efficiency. This innovative approach not only addresses current challenges, but also lays the foundation for future advances in veterinary care.